2000
DOI: 10.1002/(sici)1098-240x(200002)23:1<67::aid-nur8>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Personal and social determinants of rural nurses' willingness to care for persons with AIDS

Abstract: The purpose of this study was to investigate the individual and social determinants of rural nurses' willingness to care for people with AIDS (PWAs). Willingness to care was viewed as a function of nurses' personal attitudes about AIDS care and PWAs; the influence of normative (significant others), comparative (the nursing profession), and generalized (the rural community) reference group norms on these attitudes; and how much importance respondents placed on membership in these reference groups. Responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Rural nurses have 312 I. L. MULLINS expressed that they need to know more about AIDS and the care of PWAs (D'Augelli, 1989;Koch et al, 1991;Preston et al, 2000;. Lacking formal education about HIV/AIDS (Tessaro & Highriter, 1995) and enough information to protect them from HIV in the workplace make nurses vulnerable.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Rural nurses have 312 I. L. MULLINS expressed that they need to know more about AIDS and the care of PWAs (D'Augelli, 1989;Koch et al, 1991;Preston et al, 2000;. Lacking formal education about HIV/AIDS (Tessaro & Highriter, 1995) and enough information to protect them from HIV in the workplace make nurses vulnerable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, the nurse would not divulge that he or she provided nursing care to PWAs . Nurses are fearful that they could bring HIV home to their own children and families or that they might not be able to keep themselves from acquiring HIV in the workplace Preston et al, 2000) and die as a result (Baylor & McDaniel, 1996). In contrast, the positive effect of family support occurred when nurses who were willing to care for PWAs had significant others who were supportive .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that most nurses were willing to care for HIV/AIDS patients, and the predictors were professional education, spirituality and perceived social support, and death anxiety, feelings to preparedness and personal safety, personal attitude to nursing profession (Preston, Fortie, Kassab and Koch 2000;Sherman 2007). In sum, the predictors were mostly about the nurses' attitudes toward their organizations and profession.…”
Section: Willingness To Care For Sars Patientsmentioning
confidence: 98%
“…However, little is known about the factors that facilitate individual acts of support to people with HIV/ AIDS. Although studies in U.S. have focused on determinants of health care providers' and caregivers' willingness to care for family members with HIV/AIDS (Preston, Forti, Kassab, & Koch, 2000;Turner, Pearlin, & Mullan, 1998), our literature review did not identify any studies that investigated the factors associated community members' support to people living with HIV/AIDS in the developing world. These factors may include individual and community-level characteristics, such as the presence of leaders encouraging support to persons affected by HIV/AIDS (Figueroa, Kincaid, Rani, & Lewis, 2002).…”
Section: Introductionmentioning
confidence: 99%